Video-assisted thoracic surgery in pleural empyema: predictors of complications and treatment failures - Jagelavičius, Žymantas; Jovaišas, Vytautas; Matačiūnas, Mindaugas; Samalavičius, Narimantas Evaldas; Janilionis, Ričardas (Acta medica Lituanica, 2015)
Background. Empyema remains a challenging entity for thoracic surgeons. The aim of this study was to evaluate preoperative predictors for unsuccessful thoracoscopic empyemectomy and postoperative complications. Materials and methods. There were 71 patients prospectively included in the study during the period from January 2011 to June 2014 in whom we performed thoracoscopic empyemectomy. Two main outcomes were evaluated: conversion and complications. Preoperative factors that could predict these outcomes were analyzed. Results. Conversion to open thoracotomy was required in 25.4% of cases. Fourteen (19.7%) patients had postoperative complications. The multivariate analysis showed that the time of illness (odds ratio 1.1; confidence interval 1.1–1.2), normal temperature on admission (odds ratio 11.2; confidence interval 1.5–85.4) and frank pus found on thoracocentesis (odds ratio 6.9; confidence interval 1.6–29.4) had a significant influence on conversion from thoracoscopy to open thoracotomy. Pain (odds ratio 0.01; confidence interval